Post-mortem storage conditions and cooking methods affect long-chain omega-3 fatty acid content in Atlantic mackerel (Scomber scombrus). (15th October 2021) - Sardenne, Fany; Puccinelli, Eleonora; Vagner, Marie; Pecquerie, Laure; Bideau, Antoine; Le Grand, Fabienne; Soudant, Philippe
Highlights: Storage duration (< 24h) had a higher impact than storage temperature on EPA + DHA content in mackerel dorsal fillet. EPA + DHA and mono-unsaturated fatty acids content increased in grilled fillets. EPA + DHA losses in mackerel dorsal fillet were highly variable among individuals. Abstract: Long-chain omega-3 fatty acids such as eicosapentaenoic (EPA) and docosahexaenoic acids (DHA) are health beneficial lipids found in high concentration in pelagic fishes, including Atlantic mackerel. While EPA and DHA are sensitive to oxidation during fish storage and processing, post-mortem degradation in the first hours following fish death is poorly documented. Here, we stored fish at two temperatures (2–4 °C and 18–20 °C) and monitored EPA + DHA content in dorsal fillet 6, 12 and 24 h after fish death and after cooking (grill or steam). Storage duration was the only influencing factor, and EPA + DHA loss was faster at 18–20 °C. Six hours after fish death, EPA + DHA content decreased by 1.3 ± 1.3 mg.g −1 dw (9.6 ± 9.5% of the initial content) but it was highly variable among individuals. Handling between fishing and storage should be as short and as cool as possible to preserve EPA + DHA and food safety. Regarding cooking, EPA + DHA and mono-unsaturated fatty acids increased in grilled fillets.